2014
DOI: 10.1186/1748-717x-9-19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body-mass factors on setup displacement in patients with head and neck cancer treated with radiotherapy using daily on-line image guidance

Abstract: BackgroundTo determine the impact of body-mass factors (BMF) before radiotherapy and changes during radiotherapy on the magnitude of setup displacement in patients with head and neck cancer (HNC).MethodsThe clinical data of 30 patients with HNC was analyzed using the alignment data from daily on-line on-board imaging from image-guided radiotherapy. BMFs included body weight, body height, and the circumference and bilateral thickness of the neck. Changes in the BMFs during treatment were retrieved from cone bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…The median follow-up ranged from 29 to 38 months. Tumors were located primarily in the oropharynx [16,18,38] or the nasopharynx [17,19]. The dose delivered to the high-risk volume ranged from 66 to 76 Gy.…”
Section: Clinical Benefits Of Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The median follow-up ranged from 29 to 38 months. Tumors were located primarily in the oropharynx [16,18,38] or the nasopharynx [17,19]. The dose delivered to the high-risk volume ranged from 66 to 76 Gy.…”
Section: Clinical Benefits Of Artmentioning
confidence: 99%
“…The time point ranged from the second fraction to the 28th fraction for the first replanning session and from the 11th fraction to the 25th fraction for the second replanning session. Three studies reported the clinical results of ART in comparison with a no-ART technique [17,19,38] without randomization. Two studies were prospective [16,19], while the remaining three studies were retrospective [17,18,20].…”
Section: Clinical Benefits Of Artmentioning
confidence: 99%
“…Large anatomical variations can, however, occur during the treatment, such as weight loss [4,5], primary tumor shrinking [4], parotid gland (PG) volume reduction [6], and neck diameter reduction [7][8][9]. These modifications may generate differences between the planned and actual delivered doses, inducing the risk of PG radiation overdose [10,11] that can potentially increase the risk of xerostomia [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, weight loss greatly impacts setup error magnitude, and is consistent with previous findings in patients treated with head and neck RT. 13, 20, 21 Weight loss during RT for head and neck cancers is multi-factorial. Ionizing radiation, along with concurrent systemic chemo-therapy, induces acute mucositis and taste change.…”
Section: Discussionmentioning
confidence: 99%